Use of Animal Models for Investigating Cardioprotective Roles of SGLT2 Inhibitors - Najlaa A. Al Thani (17788493) (2023)
Sodium-glucose co-transporter 2 (SGLT2) inhibitors represent one type of new-generation type 2 diabetes (T2DM) drug treatment. The mechanism of action of an SGLT2 inhibitor (SGLT2i) in treating T2DM depends on lowering blood glucose levels effectively via increasing the glomerular excretion of glucose. A good number of randomized clinical trials revealed that SGLT2is significantly prevented heart failure (HF) and cardiovascular death in T2DM patients. Despite ongoing clinical trials in HF patients without T2DM, there have been a limited number of translational studies on the cardioprotective properties of SGLT2is. As the cellular mechanism behind the cardiac benefits of SGLT2is is still to be elucidated, animal models are used to better understand the pathways behind the cardioprotective mechanism of SGLT2i. In this review, we summarize the animal models constructed to study the cardioprotective mechanisms of SGLT2is to help deliver a more comprehensive understanding of the in vivo work that has been done in this field and to help select the most optimal animal model to use when studying the different cardioprotective effects of SGLT2is. Other Information Published in: Journal of Cardiovascular Translational Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s12265-023-10379-5